Thailand Economic Monitor, August 2017 : Digital Transformation - Ariyapruchya, Kiatipong (World Bank, Bangkok, 2018)
The Thai economic recovery has continued to broaden and gain momentum, reflecting an increase in external demand amid global growth and a recovery from severe drought. The economy grew by 3.3 percent in 2017Q1, exceeding market expectations, as farm incomes and merchandise and tourism exports rose and fiscal stimulus policies continued. Merchandise exports recorded 6.6 percent growth, the highest growth observed in the last four years, due to both rising global commodity price and trading partner growth. Economic indicators suggest that the goods export upswing became increasingly broad-based and sustained in 2017Q2. The agricultural sector expanded by 7.7 percent due to rising agricultural prices and recovery from severe drought in 2015-2016. Domestic demand remained lackluster. Both private investment and private consumption growth remained sluggish. Private investment contracted by 1.1 percent in 2017Q1, reflecting spare production capacity in the manufacturing sector although certain subsectors showed lowered spare capacity due to increased external demand. Overall credit issuance remained subdued as lending standards tightened while loans to large corporates turned positive in 2017Q1 for the first time since 2015. Loans to SMEs and households continued their deceleration trends. Softening food prices resulted in a deceleration in headline inflation. The broadening export upturn and public infrastructure plans are contributing to an improvement in Thailand’s economic outlook. Economic growth is projected to reach 3.5 percent in 2017 and 3.6 percent in 2018, as inflation is expected to return gradually to the low end of the inflation target range (1.0-4.0 percent). Continued agricultural recovery and strengthened household balance sheets will support private consumption growth while the export upswing will eventually spur manufacturing activity, capital goods import and private investment. However, a self-sustained recovery will hinge rising domestic demand supported by continued expansionary fiscal and monetary policies. Public infrastructure investments to connect lagging regions and upgrade rail through dual tracking can crowd in private investment, raise economy-wide productivity and improve investor sentiment. One specific focus area would be network slicing to ready broadband networks for the industries of the future in key requirements: latency, throughput, capacity and availability. Broadband infrastructure in Thailand will face exploding demands of data and heterogeneous requirements of different industries e.g. automotive, healthcare, logistics, retail or utilities. The network requirements for a factory with automated and flexible production systems would differ from those of a hospital doing robotic surgeries, or from the requirements of self-driving cars. To cater to these different requirements, networks will need to support different requirements for latency, throughput, capacity and availability. This would require a paradigm shift towards network slicing which can meet such needs. The European Commission is supporting a coalition of network operators1 and academic institutions to focus on network slicing for 5G, and has provided $8.9 million in funding for the initiative.